2003
DOI: 10.1254/jphs.91.313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Administration of Zonisamide, an Antiepileptic Drug, on Bone Mineral Density and Their Prevention With Alfacalcidol in Growing Rats

Abstract: Abstract. We investigated the effects of chronic administration of zonisamide, an antiepileptic agent, on bone metabolism in growing rats. Administration of zonisamide at a dose of 80 mg / kg per day, s.c. for 5 weeks significantly decreased bone mineral density (BMD) at the tibial metaphysis and the diaphysis. The percent rate of decrease in BMD at the tibial metaphysis and the tibial diaphysis was 9.2% and 5.0%, respectively. There was no significant difference between these groups in the growth of the rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
9
3
1
Order By: Relevance
“…A previous study including rats reported that the administration of ZNS at a dose of 80 mg/ kg for 5 weeks had a significant negative impact on bone density at the metaphysis and diaphysis of the tibia. 31 It was suggested that ZNS treatment elevated serum pyridinoline levels (bone resorption marker) while not affecting serum osteocalcin (a bone formation marker), which implies that ZNS might cause bone loss by accelerating bone resorption. However, there is a dearth of human studies regarding the association between ZNS and bone health.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study including rats reported that the administration of ZNS at a dose of 80 mg/ kg for 5 weeks had a significant negative impact on bone density at the metaphysis and diaphysis of the tibia. 31 It was suggested that ZNS treatment elevated serum pyridinoline levels (bone resorption marker) while not affecting serum osteocalcin (a bone formation marker), which implies that ZNS might cause bone loss by accelerating bone resorption. However, there is a dearth of human studies regarding the association between ZNS and bone health.…”
Section: Discussionmentioning
confidence: 99%
“…В экспериментальном исследо-вании A. Takahashi и соавт. [67] показано значительное сни-жение МПК в метафизе и диафизе большеберцовой кости и повышение уровня сывороточного пиридинолина (pyridinoline -PYD) на фоне приема ЗНС у крыс.…”
Section: о б з о р таблица 2 к л а с с и ф и к а ц и я п эп п о и х unclassified
“…Yet, osteoporosis has been reported in children on chronic valproic acid therapy [349,350], and long-term use of valproate and lamotrigine has been shown to be associated with reduced bone formation [351]. Animal studies using zonisamide have shown a significant decrease in BMD [352,353]; however, this has been attributed to carbonic anhydrase inhibition [346]. Limited data exist on the effects of levetiracetam on vitamin D metabolism.…”
Section: Anticonvulsantsmentioning
confidence: 99%